Age effects in NHL draftees: a data-driven review of a multi-dimensional concept - Wang, Yiru; Csiernik, Ben; Johnston, Kathryn; Baker, Joseph (Frontiers in Sports and Active Living, 2025)
IntroductionRelative age effects (RAEs) have been extensively documented in youth sports, where artificial age cut-offs create advantages for relatively older athletes throughout development. Despite four decades of research, these effects persist in many sports, particularly in ice hockey, where misaligned cut-off dates between developmental systems and professional selection create unique challenges. This study examines varying age cut-off dates, athletes' development trajectories and career outcomes in elite ice hockey.MethodsUsing one of the most comprehensive longitudinal datasets to date, the present paper also explores whether an “underdog effect” (i.e., where relatively younger athletes who survive selection barriers may achieve greater success) is present within the current sample of athletes. We analyzed the complete population of 10,485 NHL-drafted players spanning 44 years (1980-2024), examining birth quarter distributions, time to league entry, and career permanence (defined as playing ≥5 seasons and ≥268 games). Using Cox proportional hazards models and multinomial regression analyses, we investigated how birth quartile influenced player career trajectories while controlling for draft position, nationality, anthropometrics, and playing position.ResultsResults revealed that while relatively younger players were significantly underrepresented in the draft, those who were drafted demonstrated superior career trajectories. In standard analyses, Q4 players showed a faster time to enter the NHL after getting drafted (HR = 1.32, 95% CI = 1.15-1.52), and Q3 players showed significantly higher likelihood of achieving permanence (HR = 1.39, 95% CI = 1.10-1.75). When accounting for the September 15 draft cut-off (2005-2024), a “dual disadvantage” was identified within the sample, with Q3 athletes showing the strongest effects, with 61% higher likelihood of achieving permanence (HR = 1.61, 95% CI = 1.27-2.05).DiscussionThese findings support the “underdog hypothesis,” suggesting that relatively younger athletes who overcome systemic disadvantages develop compensatory skills that enhance long-term performance. Future athlete development systems should consider implementing strategies such as bio-banding or “future teams” to better support relatively younger athletes, potentially increasing talent retention across the entire player pool.